The misadventure of a dialysis catheter into the right pulmonary artery and left atrium - Joshi, Abhishek; Shah, Palakkumar; Dubey, Vivek; Kulkarni, Dwarkanath; Dattatray Aironi, Balaji; Eknath Jadhav, Uday (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2022)
Permanent catheters are widely used in haemodialysis of chronic kidney disease. Placement of these catheters is usually through the internal jugular vein or subclavian vein. Catheter placement is associated with risk of inadvertent puncture of the carotid artery, pleura and other nearby structures. These risks have been very much reduced with the use of point of care ultrasound. Even though ultrasound can guide proper puncture of the desired vessel, it cannot help in directing or following the course of the catheter after venepuncture [1]. We report a rare case of a malpositioned dialysis catheter which punctured the roof of the left atrium (LA) after going through the right pulmonary artery (RPA).